Diversity and distribution of lepidoptera-specific toxin genes in Bacillus thuringiensis strains from Argentina - Sauka, Diego Hernan; Benintende, Graciela Beatriz (2017)
A total of 268 Bacillus thuringiensis strains obtained from different sources of Argentina were analyzed to determine the diversity and distribution of the cry1, cry2, cry8, cry9 and vip3A genes encoding for lepidopteran-specific insecticidal proteins. Twin strains were excluded. Ten different profiles were detected among the 80 selected B. thuringiensis strains. Two of these profiles (cry1Aa, cry1Ac, cry1Ia, cry2Aa, cry2Ab and vip3Aa (35/80), and cry1Aa, cry1Ab, cry1Ac, cry1Ia, cry2Aa, cry2Ab and vip3Aa (25/80)) pooled 75% of the strains. The existence of this low diversity is rare, since in most of the studied collections a great diversity of insecticidal toxin gene profiles has been described. In addition, the most frequently detected profile was also most frequently derived from soil (70%), stored product dust (59%) and spider webs (50%). In contrast, the cry1Aa, cry1Ab, cry1Ac, cry1Ia, cry2Aa, cry2Ab and vip3Aa profiles were mainly detected in strains isolated from leaves (40%) and dead insect larvae (50%). Six of the identified insecticidal toxin gene profiles were discovered in strains isolated from stored product dust and leaves indicating higher diversity of profiles in these kinds of sources than in others. Some strains with high insecticidal activity against Epinotia aporema (Lepidoptera) larvae were identified, which is important to explore future microbial strategies for the control of this crop pest in the region